Dam-breach process simulation and risk assessment of outburst flood induced by the Tangjiashan landslide-dammed lake - Junxue Ma; Chong Xu; Jian Chen (Journal of Hydrology: Regional Studies)
Study region: This study focuses on the Tangjiashan landslide-dammed lake (TJSLL), located in Beichuan County, Sichuan Province, China, which experienced a large outburst flood (OF) following the 2008 Wenchuan Earthquake. The region is characterized by complex river channels and steep terrain, which significantly influenced flood dynamics. Study focus: The research aims to establish a comprehensive numerical model combining a single-dam breach model and a two-dimensional unsteady flow hydraulic model to simulate the breach process and downstream flood propagation. The study analyzes the dynamics of the Tangjiashan landslide-dammed lake outburst flood (LLOF), emphasizing flood characteristics, inundation extent, and the role of artificial drainage in mitigating flood impacts. New hydrological insights for the region: The results reveal that the peak discharges of the LLOF were 6610–6872 m³ /s, with an estimated uncertainty bound of 5500–8000 m3/s (mean value: 6750 m3/s), which is very close to the measured value of 6500 m³ /s. The proposed numerical simulations highlight significant variations in OF dynamics across different terrain types, with narrow sections experiencing faster flood progression and higher water depths. The importance of artificial drainage for mitigating flood severity is emphasized, and the findings underline the necessity of considering terrain heterogeneity and sediment transport in future flood risk assessments. This work provides valuable insights for emergency management of landslide-dammed lakes in similar regions.